2008
DOI: 10.5089/9781451869637.001
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Informal Economy in Latin America and the Caribbean

Abstract: This Working Paper should not be reported as representing the views of the IMF.The views expressed in this Working Paper are those of the author(s) and do not necessarily represent those of the IMF or IMF policy. Working Papers describe research in progress by the author(s) and are published to elicit comments and to further debate. This paper estimates the size of the informal economy for 32 mainly Latin American and Caribbean countries in the early 2000s. Using a structural equation modeling approach, we fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 16 publications
1
62
0
7
Order By: Relevance
“…Schneider and Enste [55] had estimated the informal economy of Mexico to be varying between 27 percent and 49 percent of GDP using other commonly used approaches (Physical Input or Electricity Consumption method, Currency Demand approach and the Multiple Indicators and Multiple Causes (MIMIC) model). Vuletin [56] estimated the informal economy of Mexico to be 28 percent of GDP using the MIMIC approach. Although some of the disaggregated GDP values of the states of Mexico have large residual errors, the power of the mean strengthens our argument that the informal/remittance economy of Mexico is larger than the official estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Schneider and Enste [55] had estimated the informal economy of Mexico to be varying between 27 percent and 49 percent of GDP using other commonly used approaches (Physical Input or Electricity Consumption method, Currency Demand approach and the Multiple Indicators and Multiple Causes (MIMIC) model). Vuletin [56] estimated the informal economy of Mexico to be 28 percent of GDP using the MIMIC approach. Although some of the disaggregated GDP values of the states of Mexico have large residual errors, the power of the mean strengthens our argument that the informal/remittance economy of Mexico is larger than the official estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Loayza and Sugawara (2009) showed that the size of the informal Mexican economy is about 30% of gdp, while the International Labour Organization (ilo, 1999), Schneider (2002) and Vuletin (2008) estimated that the size of the Mexican informal economy during the 1990s ranged from 30% to 40% of gdp and employed more or less the same percentage of the labour force.…”
Section: An Assessment Of the Dynamics Between The Permanent And Tranmentioning
confidence: 99%
“…24 If the central government were to regain greater control by 24 A good analysis of the importance and size of the informal economy in Latin America and the Caribbean is offered by Vuletin (2008).…”
Section: Results Of the Empirical Estimationmentioning
confidence: 99%